Faktor–Faktor yang Mempengaruhi Gangguan Perkembangan Motorik Kasar - Virmandiani, Virmandiani; Adisasmita, Asri C. (Master of Epidemiology, Faculty of Public Health, Diponegoro University, Indonesia, 2025)
Background: Gross motor skills are very important for functional independence and others developmental milestone. Delays in this domain are more pronounced than in other domains in early age, for healthy developmental trajectories, so very early detection is imperative for every parent with a newborn. This study identify risk factors that affect gross motor development in children aged 1 to 3 years.Methods: This retrospective cohort study involved 139 subjects, rehabilitation outpatient clinic. Gross motor delay was assessed using CDC (Milestone Developmental) and Gross Motor Function Classification System (GMFCS) for patient with Cerebral Palsy. Potential risk factors included: prematurity status, asphyxia, epilepsy, and parent's education.Results: 63 (45.32%) children had delays in gross motor skills, with a mean age of 27±7 months. Cox regression showed asphyxia RR=1.72; [95% CI, 1.49-1.99]; p=0.018. Epilepsy RR=1.50; [95% CI, 1.18-1.92]; p=0.004 was a factor associated with a higher risk ratio in children with gross motor delay. Prematurity was not statistically significant, which may be due to the very small number of subjects with prematurity (less than 5%). Younger children were more at risk of developing symptoms of delayed motor development. Parental education was not associated with the risk of delay.Conclusion: This study demonstrated children with asphyxia or epilepsy have higher risk of being gross motor delay. Therefore, early screening is very important in this population at risk, in order to identify potential delays so that these patients receive appropriate intervention immediately.